2022
DOI: 10.36416/1806-3756/e20210515
|View full text |Cite
|
Sign up to set email alerts
|

Post-tuberculosis lung disease: a comparison of Brazilian, Italian, and Mexican cohorts

Abstract: Objective: To evaluate lung function in a cohort of patients with a history of pulmonary tuberculosis in Brazil, as well as to evaluate the decline in lung function over time and compare it with that observed in similar cohorts in Mexico and Italy. Methods: The three cohorts were compared in terms of age, smoking status, pulmonary function test results, six-minute walk test results, and arterial blood gas results. In the Brazilian cohort, pulmonary function test results, six-minute walk test results, and arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
9
0
4
Order By: Relevance
“…We included 60 studies and identified three additional studies from reference lists of the included studies. In total, 63 studies with 41,014 patients with PTB were included 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 . Of the 63 studies, 61 were unique study populations (two pairs of studies reported different post-TB assessments in the same study population 52 , 53 , 73 , 99 ).…”
Section: Resultsmentioning
confidence: 99%
“…We included 60 studies and identified three additional studies from reference lists of the included studies. In total, 63 studies with 41,014 patients with PTB were included 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 . Of the 63 studies, 61 were unique study populations (two pairs of studies reported different post-TB assessments in the same study population 52 , 53 , 73 , 99 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent comparison of three different cohort studies involving PTLD patients in Brazil, Italy, and Mexico, pulmonary function tests showed different results, the majority of which showed obstructive, mixed, and normal patterns, respectively. 23 …”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, whenever plethysmography or lung volume measurements are feasible, they should complement spirometry to confirm obstructive, restrictive, or even mixed patterns of pulmonary disease since the type of ventilatory defect can be heterogeneous and vary in different populations. 23 …”
Section: Assessment Of Ptldmentioning
confidence: 99%
“…Eles podem ter déficits de função pulmonar (obstrução, restrição ou padrões mistos), tendo um risco duas vezes maior de apresentar anormalidades espirométricas do que a população em geral, e aproximadamente 10% desses pacientes podem ter perdido mais da metade de sua função pulmonar. (2,4,5) Além disso, esses pacientes podem apresentar sintomas respiratórios persistentes, como tosse residual e dispneia, além de redução da capacidade de exercício e da qualidade de vida. (2,6) Além disso, foi demonstrado que sobreviventes da tuberculose têm uma taxa de mortalidade pós-tratamento de longo prazo quase três vezes maior do que a população geral, com a maioria das mortes ocorrendo no primeiro ano após o término do tratamento.…”
unclassified
“…They may have lung function deficits (obstruction, restriction, or mixed patterns), having a two-fold greater risk of presenting with spirometric abnormalities than the general population, and approximately 10% of these patients may have lost more than half of their lung function. 2 , 4 , 5 In addition, these patients may have persistent respiratory symptoms, such as residual cough and dyspnea, in addition to reduced exercise capacity and quality of life. 2 , 6 Furthermore, it has been shown that tuberculosis survivors have a long-term post-treatment mortality rate almost three times higher than the general population, with most deaths occurring in the first year after the end of treatment.…”
mentioning
confidence: 99%